2010
DOI: 10.1007/s11270-009-0309-0
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effect of Saline Solution on the Extraction of the Moringa oleifera Seed’s Active Component for Water Treatment

Abstract: Several coagulants/flocculants have been studied in order to remove the color and turbidity of raw water, employing natural ones demonstrated advantages in relation to chemicals. Moringa oleifera Lam is a natural polymer that has been gaining prominence in water treatment. It acts as a clarifying agent, providing a cationic protein that destabilizes the particles contained in a liquid medium. The main objective of the present work is to study the efficiency in terms of removing color and turbidity of raw water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
1
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 120 publications
(77 citation statements)
references
References 14 publications
4
51
1
13
Order By: Relevance
“…The differences may be due to the different preparation procedures of the moringa solution, by aqueous or saline extraction, as well as the different concentrations of the stock solution of moringa. In both studies, the coagulant properties of the moringa appear to be more efficient in water of high initial turbidity, in agreement with other literature reports (Ndabigengesere et al, 1995;Madrona et al, 2010). Ndabigengesere et al (1995), applying an aqueous solution of 5% moringa seeds to synthetic turbid water (kaolin added to tap water) with initial turbidity of 426 NTU, obtained removals from 80 to 90% and reached the optimum concentration of 500 mg/L of coagulant solution.…”
Section: Process Of Coagulation/flocculation With Moringa Followed Bysupporting
confidence: 90%
See 2 more Smart Citations
“…The differences may be due to the different preparation procedures of the moringa solution, by aqueous or saline extraction, as well as the different concentrations of the stock solution of moringa. In both studies, the coagulant properties of the moringa appear to be more efficient in water of high initial turbidity, in agreement with other literature reports (Ndabigengesere et al, 1995;Madrona et al, 2010). Ndabigengesere et al (1995), applying an aqueous solution of 5% moringa seeds to synthetic turbid water (kaolin added to tap water) with initial turbidity of 426 NTU, obtained removals from 80 to 90% and reached the optimum concentration of 500 mg/L of coagulant solution.…”
Section: Process Of Coagulation/flocculation With Moringa Followed Bysupporting
confidence: 90%
“…Madrona et al (2010) evaluated the extraction of the coagulant protein in the presence of potassium chloride (KCl) at different concentrations. The authors have shown that greatest coagulation efficiencies are achieved with KCl 1 mol/L, reaching nearly 100% removal of color and turbidity from water with initial turbidity of 850 NTU.…”
Section: Moringa Oleiferamentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, natural or synthetic polymeric substances are used as coagulants alone or as coagulant aids together with metal salts. A number of natural materials have coagulating abilities such as chitosan, starch and alginate (Ahmad et al 2006;Devrimci et al 2012;Divakaran and Pillai 2002;Guibal and Roussy 2007;Labille et al 2005;Madrona et al 2010;Qudsieh et al 2008;Sand et al 2010;Tripathy and Singh 2001). Natural polymers are advantageous because they are less toxic and more biodegradable (Bolto and Gregory 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Há procedimentos manuais nos quais se utiliza pilão para trituração das sementes (Okuda et al, 1999;Okuda et al, 2001) podendo ocorrer, após trituração, peneiramento do pó obtido para retirada de partículas maiores (Paterniani et al, 2009;Paterniani et al, 2010). Outros autores adotam a metodologia com obtenção do pó utilizando liquidificador doméstico ou (Ndabigengesere et al, 1995;Katayon et al, 2006) e até mesmo preparo da solução diretamente no liquidificador (Madrona et al, 2010).…”
Section: Introductionunclassified